An initial assessment of the robust and compact hybrid environmental lidar (RACHEL) - Povey, A; Peters, D; Grainger, R; Rees, D; Agnew, J (International Society of Acoustic Remote Sensing of the Atmosphere and Oceans, 2016)
The Robust And Compact Hybrid Environmental Lidar (RACHEL) is a 355nm, 4-channel Raman lidar system that has been developed for unattended, continuous measurement of the distributions of particulates, water vapour, and other pollutants in the boundary layer and troposphere, including the capacity for scanning the full hemisphere. The system has been designed to be portable and low-cost, providing the potential to investigate a wide range of environments with a single instrument. Deployment at the beginning of 2010 at the STFC Chilbolton Observatory has provided a unique opportunity to cross-compare the instrument against the numerous lidar and radar systems stationed at the observatory and to evaluate the implementation of various measurements into the data evaluation, such as radiosondes, radiometers, and aircraft observations. The system was deployed during the Eyjafjallajökull eruption of April 2010, observing the appearance and evolution of the ash plume over southern England.